METODE FLUSHING S-A-S & TEKNIK PULSATILE PUSH PAUSE MENURUNKAN ANGKA KEJADIAN FLEBITIS KIMIA - Nur Hidayah; Indah Nur Imamah; Rivan Firdaus (Jurnal Cakrawala Ilmiah, 2023)
According to the cause of phlebitis; Chemical phlebitis is an inflammatory reaction that occurs in blood vessels caused by drugs and fluids that can irritate or be directly dangerous to blood vessels. The research aims to determine the effect of the Saline-Administration-Saline (S-A-S) method & pulsatile push pause technique on the incidence of chemical phlebitis levels that may be found in patients who receive concentrated drug & electrolyte therapy. This design of this study was a quasi experiment with control groups pretest-posttest design. Respondents were taken by random sampling as many as 32 patients in the Bougenvile inpatient room at Taman Husada Hospital, Bontang. Data were collected with an observation instrument sheet for phlebitis incidents. Visual Infusion Phlebitis (VIP) Score; measuring tool by Jackson (1997). Data analysis used Mann Whitney. The result showed that after the intervention, a significant difference was found in the incidence of phlebitis/phlebitis grade scores between the intervention group and the control group with a p value of 0.021 (p < 0.05). Giving flushing saline using the Saline-Administration-Saline (S-A-S) method & pulsatile push pause technique has been proven to reduce the incidence of chemical phlebitis.